Cinepalco: o espaço cênico intertextual - Sulzbach, Ândrea Cristina (2015)
This work has as object of study the theatrical language present in four films which appropriate intertextual foundations in the construction of scenic and representative structure. The selected films are Dogville ( Lars Von Trier, 2003) , Caesar Must Die (Paolo and Vittorio Taviani , 2012) , You Do not Seen Nothing ( Alain Resnais , 2012) and Anna Karenina ( Joe Wright , 2012) . The overall goal is to identify the elements present in the creative process, in these films, which interact with each other. The specific objectives deal with the deepening of perceived interconnections, the main unfolding the presence of Performing Arts, is in unconventional spaces , either in inserts in mainstream cinema . The initial study analyzes the approach and the visual architecture of directors within specific periods film who contributed their works. The movements were identified Dogma 95, Neorealism, Nouvelle Vague and Classic Cinema. The comparative methodology focuses on the counterpoint between the three European assemblies with the American Anna Karenina , from the scenic production. The hypothesis is that the ownership of theatrical language as intertext provides a reflective film which is designed in various ways , such as physical structure, such as action / staging , as metatext and as a stage show with effect respectively , in the four corpus of films. For the study of the scenic area with distancing effect are used the definitions of Bertolt Brecht. The Constantin Stanislavski method used for the study of naturalistic staging. The general analysis of scenic elements is based on Jean- Jacques Roubine settings and Jacques Aumont. The film opacity and transparency follows the precepts of Ismail Xavier. The concept of intertextuality of Julia Kristeva and the Guy Debord's spectacle complete the theoretical framework.